A decade teaching and researching in Food Education for Teachers - Rodrigo Vega, Maximiliano; Ejeda Manzanera, José Manuel; Caballero Armenta, Manuela (Revista Complutense de Educación, 2013)
The improvement of food education in a Group of teachers contributes to a field of interest due to the strategic importance of preventing obesity now prevalent. In fact since the academic year 1997 /1998 we have been collaborating by introducing a new lecture in the University of Education from the UCM in Madrid, which is related to this topic. At the same time, we have been carrying out research on both, the development of knowledge and the description of food behaviour habits from different groups of future teachers that we have worked with. Due to the fact that this research took place more than a decade ago since having started all this research and educational action, we have deemed it necessary to engage in updated research, which reflects what situation the didactic design faced nowadays in food education is actually in for teachers, and which are the main research data items that perform as keys for our research, thus the main future challenges that we have.